Pemberdayaan Masyarakat Dalam Pemanfaatan Tanaman Obat Keluarga (TOGA) di PKK Dasawisma Keluarahan Sempaja Selatan - Gabriella Chandy Simangunsong (Lembaga Pengembangan Kinerja Dosen, 2024)
The empowerment carried out by Dasawisma’s Family Welfare Empowerment, Sempaja Selatan Subdistrict is an activity that functions as an effort to cultivating plants on limited land. This research discusses (1) describing the process of empowering the use of medicinal plants and (2) identifying the factors that influence the empowerment of the use of medicinal plants in Dasawisma’s Family Welfare Empowerment. This study used qualitative research methods. Data collection techniques are through observation, interviews and documentation. Data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. Validity of data using triangulation techniques and techniques. The results of this research consist of: (1) Empowerment of the Use of Medicinal Plants which includes: a) awareness stage based on the results of identification and discussions carried out by Dasawisma’s Family Welfare Empowerment members with the Village Head b) capacity building stage carried out by socialization, introduction, training, and determining learning models for medicinal plants and c) the empowerment stage involves distributing tasks and empowering PKK members to become independent. 2) Factors that support empowerment are the unity of members who want to develop, trainers who are appropriate to their field, and funds fully supported by the village head.